2016
DOI: 10.15376/biores.11.3.6162-6173
|View full text |Cite
|
Sign up to set email alerts
|

The Retention and Drainage Behavior of Cross-linked Gelatin with Glutaraldehyde in a Papermaking System

Abstract: A type of novel retention aid, cross-linked gelatin, was prepared using lowgrade industrial gelatin as the raw material and glutaraldehyde as the crosslinking agent. The structure of cross-linked gelatin was characterized according to the crosslinking degree, isoelectric point, Fourier transform infrared spectroscopy, and ultraviolet-visible spectroscopy. The results indicated that the crosslinking reaction was successfully performed between the primary amine group of gelatin and the aldehyde group of glutaral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
2
4
0
1
Order By: Relevance
“…Fourier transform infrared (FT-IR) spectra (Figure c and Figure S2f) provide evidence of the successful combination of the zwitterionic polymer (PEI-S) and BNF. After exposure to GA vapor, the PEI-S was crosslinked, proven by the presence of the peaks at 1538 cm –1 , indicating the stretching vibration of imine groups (CN) . The new peak around 1198 cm –1 attributed to stretching vibration of sulfonate groups appeared in the FT-IR spectra of both the PEI-S polymer and PEI-S@BNF-xh membranes (with x h GA crosslinking), confirming the existence of the zwitterionic structure, which could also be evidenced from scanning electron microscope energy-dispersive X-ray spectroscopy (SEM–EDX).…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Fourier transform infrared (FT-IR) spectra (Figure c and Figure S2f) provide evidence of the successful combination of the zwitterionic polymer (PEI-S) and BNF. After exposure to GA vapor, the PEI-S was crosslinked, proven by the presence of the peaks at 1538 cm –1 , indicating the stretching vibration of imine groups (CN) . The new peak around 1198 cm –1 attributed to stretching vibration of sulfonate groups appeared in the FT-IR spectra of both the PEI-S polymer and PEI-S@BNF-xh membranes (with x h GA crosslinking), confirming the existence of the zwitterionic structure, which could also be evidenced from scanning electron microscope energy-dispersive X-ray spectroscopy (SEM–EDX).…”
Section: Resultssupporting
confidence: 52%
“…After exposure to GA vapor, the PEI-S was crosslinked, proven by the presence of the peaks at 1538 cm −1 , indicating the stretching vibration of imine groups (C N). 28 The new peak around 1198 cm −1 attributed to stretching vibration of sulfonate groups appeared in the FT-IR spectra of both the PEI-S polymer and PEI-S@BNF-xh membranes (with x h GA crosslinking), confirming the existence of the zwitterionic structure, which could also be evidenced from scanning electron microscope energy-dispersive X-ray spectroscopy (SEM−EDX). As shown in Figure 1d, about 5 wt % (2 at%) of the sulfur elements have been detected, and they were homogenously distributed along the entire nanofibrous membranes (inset of Figure 1d).…”
Section: Resultsmentioning
confidence: 61%
“…It displays the characteristics bands of gelatin: the large band around 3300 cm −1 corresponds to the amide-A peak (N H stretching band) as well as free water; the amide I (C O) is detected from the peak around 1630 cm −1 , the amide II (N H and C H bands) is represented by the peak around 1550 cm −1 , and the small peaks at around 1240 cm −1 matches the amide III bonds (C N, N H). 39,40 No others bands are present in the spectrum, thus it can be concluded that the polyethylene glycol is correctly washed and do not affect the chemical composition of gelatin beads. It confirms that PEG molecules are not inserted in the gelatin beads.…”
Section: Ftir Analysismentioning
confidence: 90%
“…Gambar 6B menunjukkan adanya serapan pada bilangan gelombang 1622 cm -1 yang mengindikasikan adanya interaksi antara glutaraldehid dengan protein. Serapan pada bilangan gelombang 1620,21 cm -1 menunjukkan keberadaan senyawa Schiff base (Sirumapea & Anggraini, 2016;You et al, 2016;Jadhav et al, 2017). Senyawa Schiff base merupakan senyawa yang mengandung gugus fungsional azometin (C=N) hasil kondensasi amina primer dengan senyawa karbonil.…”
Section: Kodeunclassified